THE USE OF INDONESIAN ENGLISH CODE MIXING ON INSTAGRAM CAPTIONS - Nuraeni, Bani Lisa; Farid, Mochammad Zhafran; Cahyati, Sri Supiah (PROJECT (Professional Journal of English Education), 2018)
Recent studies on intrasentential code-switching or code mixing (CM) show the functional separation of two languages to be a legitimate, highly structured bilingual communicative device with its own syntactic and sociolinguistic constraints.This research investigates the use of code mixing on instagram.The study aims to find out kind of  code mixing used on Instagram users in their caption and to find out  how many code mixing code used by instagram users in their caption. This research applies descriptive qualitative method. The data of this research are Indonesian – English code mixing on Indonesian Instagram users posting and the information of the reasons of using code mixing. The data are taken from the Indonesian Instagram users posting. The data are analyzed based on the linguistic form of code mixing by Suwito’s theory and the reasons of code mixing by Hockett’s theory.Keyword: Code Mixing, Instagram, Linguistic form